Analisis Strategi Pengembangan BMT Agam Madani di Banuhampu, Kabupaten Agam - Dafiar Syarif; Delli Ridho Hayati; Mursal Mursal; Suci Mahabbati; Muhammad Fauzi (Universitas Islam Raden Rahmat, 2022)
This study aims to identify internal and external factors of Baitul Maal Wat Tamwil Agam Madani in Banuhampu districts. The problem in this study is to see the strategy for developing Baitul Maal Wat Tamwil. The data that is used in this study uses primary data that has been collected using question and analyzed using internal and external factor analysis also SWOT quantitative analysis, SWOT stage assumptions the effective strategy that maximize strengths and opportunities and minimized weaknesses and threats. The finding of this research showed that BMT (1) Development strategy through improving the quality of human resources owned by BMT, (2) Development strategy through improving the quality of organizational management, (3) Development strategy through providing infrastructure and technology needed in service. This study also revealed that in the strategy for improving the quality of organizational management other strategies are quite important for future BMT development.